LANDSLIDE WARNING SYSTEM USING GSM - Gokul, U.; Sivagami, Arasu (International Journal of Psychosocial Rehabilitation, 2020)
Landslide is an important and very natural calamity which occurs unexpectedly due to large amount of rainfall. This is really a big threat to human life and property. We cannot stop this natural disaster but still we can predict whether this disaster will come or not. Landslide will come mainly in the areas of hilly regions surrounded by many mountains. These mountains will be mostly a tourist places with lots of houses and shops and many people from outside place will come and go. In hilly areas the rainfall will be very high. Because of this the landslide may happen at any time. So to predict the early stages of landslide we are going to design a wireless sensor network. This wireless sensor network will have sensors such as soil moisture and rain sensors. These sensors will be connected to a microcontroller which will collect the data from these sensors. A GSM module is also connected to microcontroller which will send sms which the value of the sensors crosses the threshold value. Thus the life and property of humans can be saved.